The eternal Body - Clevis, Krien; Santing, Catrien (Budel : Damon, 2004)
De Blaauw, Dible; Caus, Wim ; VanDijck, José ; Clevis, Krien ; De Haan, Nathalie ; De Jong, Folkert ; Hagoort, Erik ; Visser, Anook-Cléonne ; Damen, Ester Eva ; et al.
boek